Preparation and Deodorization Performance of Sludge Straw Composite Carbon and Carbon Paper - ZHENG Menglong; LI Youjing; YANG Ying; LI Fen (Journal of Harbin University of Science and Technology, 2023)
In order to study the application mode of biochar, excess sludge and straw were used as raw materials and KOH activation process and coating method were adopted, which prepared composite carbon and composite carbon papers, the preparation process parameters were optimized and the performance of adsorbing H2 S odor gas was studied. The results show that the deodorization effect of the carbon material prepared by KOH as the activator of sludge straw was obviously better than that of urea. When the ratio of activated sludge∶ straw∶ KOH is 5∶ 5∶ 10 and the carbonization temperature is 550℃ , the adsorption duration of H2 S is the longest, which is 120 min. After the composite carbon is made into carbon papers, because the adhesive blocks part of the pores of the composite carbon, the deodorization performance of carbon papers is decreased slightly, but it can also reach 36 minutes and when the mass ratio of composite carbon, dispersant and binder is 25∶ 1∶ 3, the adsorption properties are the best. The structural analysis shows that there are a large number of holes on the surface of composite carbon and carbon papers. The structural analysis shows that there are a large number of pores on the surface of the composite carbon and carbon papers, as well as there are oxygen-containing and nitrogen- containing functional groups such as O-H, C = O, N-H, C-O. These structures play a positive role in the adsorption of H2 S.